2012
DOI: 10.1080/1750984x.2011.631027
|View full text |Cite
|
Sign up to set email alerts
|

Music in the exercise domain: a review and synthesis (Part II)

Abstract: Since a 1997 review by Karageorghis and Terry, which highlighted the state of knowledge and methodological weaknesses, the number of studies investigating musical reactivity in relation to exercise has swelled considerably. In this two-part review paper, the development of conceptual approaches and mechanisms underlying the effects of music are explicated (Part I), followed by a critical review and synthesis of empirical work (spread over Parts I and II). Pre-task music has been shown to optimise arousal, faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
213
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(219 citation statements)
references
References 59 publications
5
213
1
Order By: Relevance
“…Extant work has shown that music use is not effective for some people under certain circumstances (e.g., while learning new skills) and might even be contraindicated in some instances (e.g., when it might distract users from safety-relevant information, such as on public roads; see Karageorghis & Priest, 2012a, 2012b for a review). Also, a "vitamin model" wherein a particular piece of music can be prescribed to engender certain perceptual, cognitive, or emotional responses in a listener, does not apply to this field of scientific endeavour (Sloboda, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extant work has shown that music use is not effective for some people under certain circumstances (e.g., while learning new skills) and might even be contraindicated in some instances (e.g., when it might distract users from safety-relevant information, such as on public roads; see Karageorghis & Priest, 2012a, 2012b for a review). Also, a "vitamin model" wherein a particular piece of music can be prescribed to engender certain perceptual, cognitive, or emotional responses in a listener, does not apply to this field of scientific endeavour (Sloboda, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the effects of music were expounded in a recent two-part review paper (Karageorghis & Priest, 2012a, 2012b therefore only an overview will be provided here: The limited capacity of the nervous system has a bearing on the effects of music on attention (see Rejeski, 1985). These limitations restrict the degree to which the human organism is able to process music during high-intensity activity when fatigue-related signals overwhelm the afferent nervous system.…”
Section: Mechanisms Underlying the Effects Of Music During High-intenmentioning
confidence: 99%
See 1 more Smart Citation
“…A slow tempo will benefit an endurance exercise, 16 and a fast tempo will improve the work load during exercise. 17 Moreover, listening to music was demonstrated to be beneficial in various situations such as during physical exercise, 15,18 physiotherapy sessions for subjects with cystic fibrosis, 19 and rehabilitation of elderly subjects. 20 To our knowledge, its effect was not investigated during a group pulmonary rehabilitation session.…”
Section: Introductionmentioning
confidence: 99%
“…In exercise and sport settings, the use of music has become extremely widespread (20). At first, Music was used in group exercises but it extended from group to individual exercise when personal listening devices such as Nike's Personal Sport Audio™ and iPod™ reached the mass market (27).…”
Section: Introductionmentioning
confidence: 99%